2005
DOI: 10.1002/jnr.20612
|View full text |Cite
|
Sign up to set email alerts
|

CCL2 and CXCL1 trigger calcitonin gene-related peptide release by exciting primary nociceptive neurons

Abstract: Chemokines are important mediators in immune responses and inflammatory processes. Calcitonin gene-related peptide (CGRP) is produced in dorsal root ganglion (DRG) neurons. In this study, CGRP radioimmunoassay was used to investigate whether the chemokines CCL2 and CXCL1 could trigger CGRP release from cultured DRG neurons of neonatal rats and, if so, which cellular signaling pathway was involved. The results showed that CCL2 and CXCL1 ( approximately 5-100 ng/ml) evoked CGRP release and intracellular calcium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
135
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(146 citation statements)
references
References 47 publications
9
135
1
1
Order By: Relevance
“…CCL2 has been proven to cause pain in animal models or articular inflammation in several animal studies. [11][12][13][14][15] One recent study showed that CCR2/CCL2 plays a key role in balancing the bone remodelling process. 28 All these factors indicate CCL2 may act in pathogenesis or progression of OA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CCL2 has been proven to cause pain in animal models or articular inflammation in several animal studies. [11][12][13][14][15] One recent study showed that CCR2/CCL2 plays a key role in balancing the bone remodelling process. 28 All these factors indicate CCL2 may act in pathogenesis or progression of OA.…”
Section: Discussionmentioning
confidence: 99%
“…12 Studies have also shown CCL2 could induce pain-related behaviours in rodents. [13][14][15] Since CCL2 is present in the osteoarthritic joint, it may serve as potential pain mediator in OA. Besides, recent studies have demonstrated that CCL2 increases vascular cell adhesion molecule 1 (VCAM-1) expression in human OA synovial fibroblasts via a cascade of signalling pathways, and CCL2-induced VCAM-1 expression promoted monocyte adhesion to human OA synovial fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, inhibition of PKCε decreases capsaicin-induced release of glutamate and CGRP in isolated spinal cords (52). In addition to topical capsaicin, chemokines stimulate the release of CGRP from afferent neurons in a PKC dependent manner (53). One potential mechanism by which pre-synaptic PKC activity can augment neurotransmitter release is via PKC-dependent sensitization of voltage-dependent L-type Ca2+ channels (54).…”
Section: B the Primary Afferent-spinal Cord Synapsementioning
confidence: 99%
“…Chemokine receptor induced calcium signalling is not completely understood. Several inhibitors, like omega-conotoxin GVIA (an Ntype calcium channel blocker), thapsigargin (a sarcoendoplasmic reticulum Ca 2+ -ATPase inhibitor) as well as phospholipase c and protein kinase c inhibitors seem to 4 affect CCL2 and CXCL1 induced calcium response [15], giving some indication about how chemokine receptor activation is coupled to calcium signalling. However for CCR5, no characterisation of the mechanisms for the intracellular calcium release after receptor activation has been shown so far.…”
Section: Introductionmentioning
confidence: 99%